COMPLEX TECHNOLOGY OF IMPROVEMENT THE PROCESS OF AIRCRAFT MAINTENANCE EFFICIENCY - A. R. Aleksanyan; I. A. Fainburg; A. D. Evdokimova (Научный вестник МГТУ ГА, 2018)
In the conditions of contemporary world market, the maintenance process to keep the required level of aircraft serviceability in airlines should be economically efficient in relation to labour, time and material expenses. The solution of the problem can be achieved by planning and managing the activity of airlines with the aim to improve the efficiency of civil aircraft maintenance process. Planning and implementation of activities for process improvement of aircraft maintenance efficiency in particular such factors as aircraft (A/C) reliability and safety, flight regularity and A/C timewise operation efficiency, A/C intensities and economy require collaboration and interaction of developer, manufacturer and operator. This work proves the need to develop the planning and performance technology of actions related to the airlines activity allowing step by step according to developer, manufacturer and operator activities to establish the cooperation and influence on aircraft serviceability, thereby increasing the maintenance process by all possible managing actions. The complex technology to improve the efficiency of aircraft maintenance process including activities on “A/C Reliability”, “Technology”, “Personnel”, “Equipment”, “Materials” has been developed with the aim to increase the A/C fleet serviceability level. The complex technology is represented as a route technology with brief description of destinations in the route chart with input/output indications at each stage.The advantages of complex technology application are shown in the example of improving one of the efficiency measures in aircraft maintenance process.